Monogenean Parasite Infections in Asian Seabass, Lates calcarifer (Bloch, 1790) during Crop Production in Earthen Pond Culture at Surat Thani, Thailand - Sornkham, Supannee; Laudee , Pongsak; Kamchoo, Kanda (Journal of Food Health and Bioenvironmental Science, 2023)
This study aimed to identify monogenean parasites in Asian seabass (Lates calcarifer) and to assess infection rates in the host fish in an earthen pond culture during crop production in Surat Thani province, Thailand. One hundred fish were examined for parasite infections from July to November, 2017. Two species of monogeneans, Laticola paralatesi and Laticola seabassi, were detected on gill filaments. The highest 75% prevalence was observed in September. The highest mean intensity of L. paralatesi was recorded in September (5.8 parasites per fish). L. seabassi was detected at the highest mean intensity in November (2.6 parasites per fish), which was significantly different among the five months (p < 0.05). Moreover, the fish size was not significantly correlated with L. paralatesi, but there was a significant positive correlation between the weight of fish and the number of L. seabassi (r = 0.928; p < 0.05). This study corroborates that Laticola spp. is commonly found in Asian seabass, with parasite transmission from fish to fish, and the larval stage from wild infected fish live in natural water sources and is spread to fish ponds. The present work reveals monthly profiles of infestations by monogenean parasites in earthen pond culture and the results can be applied in fish health management. This is the first report on monogenean parasite infections in Asian seabass, in earthen pond cultures in southern Thailand.